PENGARUH SISTEM MANAJEMEN KINERJA TERHADAP KEPUASAN KARIR DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI PADA PT KRAFT ULTRAJAYA INDONESIA - Giovani Marto Surexa Waka (Jurnal Manajemen, 2017)
This study was conducted with the aim to determine the perceptions of respondents about the effect of performance management systems on career satisfaction and how the influence of job satisfaction mediates the relationship between performance management systems and employee career satisfaction at PT Kraft Ultrajaya Indonesia. This study uses primary data obtained directly from respondents by distributing questionnaires. The population of this study were all managerial employees of PT Kraft Ultrajaya Indonesia with a sample of 50 PT Kraft Ultrajaya Indonesia managerial employees. The sampling technique uses convenience sampling. This study contains a test of the effect of independent variables on the dependent variable and analysis of mediation effects. The findings show that the performance management system, job satisfaction, and career satisfaction are good. Job satisfaction variables are proven to mediate the relationship between performance management systems and career satisfaction. All relationships between variables have a significant relationship, except the relationship between performance management systems to career satisfaction that does not have a significant relationship. PT Kraft Ultrajaya is also advised to improve its performance management and pay more attention to aspects of rewards that are in line with employee achievement.